IDENTIFICATION OF Aspergillus sp IN PULMONARY TUBERCULOSIS PATIENTS WITH ADVANCED TREATMENT IN KABILA HEALTH CENTER, BONE BOLANGO REGENCY - Rian Ariandi; Syam S. Kumadji; Wiharsri (LPPM Universitas Bina Mandiri Gorontalo, 2022)
The purpose of this study was to determine the types of Aspergillus sp that attack pulmonary tuberculosis patients who were currently undergoing advanced treatment at the Kabila Health Center, Bone Bolango Regency. The method used in this research was a qualitative approach with a descriptive type of research. The type of data used was primary data in the form of examination results of Aspergillus sp. at the Microbiology Laboratory of Bina Mandiri University, Gorontalo, while secondary data was in the form of observations in the form of medical records of pulmonary tuberculosis patients who undergo advanced treatment at the Kabila Health Center, Bone Bolango Regency. Sources of data were collected using questionnaires and documentation results. The sampling technique in this study used the Total Sampling technique, with a total sample of 13 people. Based on the results of this study, from 13 sputum samples examined, it is found that 4 pure isolates of Aspergillus fumigatus are isolated.